Evaluation of a School-Based Dissemination of the Movement Guidelines for Young Children in Hong Kong: Study Protocol - Capio, Catherine M (Archīum Ateneo, 2021)
Background Healthy movement behaviors in early childhood are believed to track to adulthood, potentially imparting protective benefits against non-communicable diseases. Highlighting the collaborative and complementary roles of parents and educators in promoting health of young children, this study aims to enable parents and teachers to successfully promote healthy movement behaviors in young children. Guidelines for physical activity, sedentary screen time, and sleep of children aged 2 to 6 years will be systematically disseminated to parents and teachers of children enrolled in early childhood education centers (ECECs) in Hong Kong. An evaluation will be conducted to assess the implementation process and the outcomes of the dissemination of said guidelines. Methods The evaluation will include formative and summative components to examine the implementation (i.e., process evaluation) and the outcomes (i.e., outcome evaluation). Participants include teachers, parents, and children from ECECs in Hong Kong. The process evaluation will be guided by the RE-AIM framework (i.e., reach, efficacy, adaptation, implementation, maintenance). Data gathering and analysis will take a mixed-methods triangulation design - convergence model. The outcome evaluation consists of a non-randomized observational study, using quantitative data from questionnaires and accelerometers. The primary outcome to be measured is the extent to which children meet the guidelines for physical activity, sedentary screen time, and sleep; the secondary outcome is teachers’ and parents’ knowledge and awareness of the guidelines. Discussion Young children who engage in healthy movement behaviors are likely to become adults who will have the disposition to engage in behaviors that have protective effects against non-communicable diseases. The findings of this evaluation are expected to contribute to improving the strategies of systems and government agencies that aspire to promote healthy movement behaviors of young children.